A descriptive study of inpatient admissions for cerebrovascular disease at a tertiary hospital in KwaZulu-Natal, South Africa - Moodley, Y.; Adam, J.K. (SA Heart Journal, 2021)
Background: We sought to provide a descriptive report of inpatient admissions for cerebrovascular disease (CVD) at a tertiary hospital in KwaZulu-Natal, South Africa. Methods: We conducted a retrospective, descriptive study involving 1 017 patients admitted to the Inkosi Albert Luthuli Central Hospital for treatment of CVD during 2005 - 2015. Patients were identified using the hospital’s electronic administrative system. Demographics, inpatient length of stay, surgical procedures, and survival status at discharge were also obtained for each patient. Descriptive statistics were used to analyse the data. Results: The median age of CVD patients was 50.0 years, and 50.4% were male. The median inpatient length of stay was 13.0 days. Surgery was performed in 38.8% of patients. The mortality rate was 22.5%. Conclusion: The resource burden that CVD places on tertiary healthcare services and the high mortality in afflicted patients highlights the need for effective primary and secondary prevention interventions in our setting.